2018
DOI: 10.1016/j.neuropharm.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of alpha 5 nicotinic acetylcholine receptors subunit alters ethanol-mediated behavioral effects and reward in mice

Abstract: Evidence suggests that there is an association between polymorphisms in the α5 nicotinic acetylcholine receptor (nAChR) subunit and risk of developing alcohol dependence in humans. The α5 nAChR subunit has also recently been shown to modulate some of the acute response to ethanol in mice. The aim of the current study was to further characterize the role of α5-containing (α5*) nAChRs in acute ethanol responsive behaviors, ethanol consumption and ethanol preference in mice. We conducted a battery of tests in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Alcoholics are three times more likely to smoke than the general population [3], and at higher risk to die from smokingrelated illnesses than from alcohol-related causes [35]. Several mechanisms have been proposed to underlie alcohol and tobacco addiction comorbidity, including cross-cue conditioning, cross-tolerance and -reinforcement [36,37] and nicotinic modulation of alcohol effects [30,38,39]. Both alcohol and nicotine can modulate signalling pathways implicated in addiction through both distinct and common molecular targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholics are three times more likely to smoke than the general population [3], and at higher risk to die from smokingrelated illnesses than from alcohol-related causes [35]. Several mechanisms have been proposed to underlie alcohol and tobacco addiction comorbidity, including cross-cue conditioning, cross-tolerance and -reinforcement [36,37] and nicotinic modulation of alcohol effects [30,38,39]. Both alcohol and nicotine can modulate signalling pathways implicated in addiction through both distinct and common molecular targets.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, EtOH has been shown to act as an allosteric modulator of nAChRs and suggested to alter the balance between activation and desensitization of nAChRs caused by nicotine [30]. Previous studies reported no alterations in EtOH intake in α5 knock-out (KO) mice in a drinkingin-the-dark paradigm [38,40], although EtOH intake was actually decreased in these mice, in a similar paradigm, after a restraint stress [38]. The same study also reported decreased EtOH-induced conditioned place preference in α5 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies associate the α5 gene to smoking and lung cancer through the existence of a polymorphism that produces a protein variant of α5 (D398N) [1]. In mice, α4 -/and β2 -/genotypes fail to self-administer nicotine, while α5 -/genotype displays a unique altered behavior towards nicotine, with partly reduced nicotine-related behaviors [2][3][4] and also towards ethanol, whose effects are partly enhanced [5], together with anxiety-related behaviors [6]. In rats, a recent study also highlighted a phenotype linked to nicotine and alcohol relapse processes [7,8].…”
Section: Main Text Introductionmentioning
confidence: 99%
“…With respect to alcohol, α 5 KO mice show enhanced alcohol-induced hypothermia and anxiolysis, but reduced ethanol place preferences and reduced ethanol intake in the DID with restraint stress paradigm ( Dawson et al, 2018 ). By contrast, α 5 KO mice did not differ from wild type controls in the DID paradigm ( Santos et al, 2013 ), although they were more sensitive to the acutely sedating effects of ethanol ( Santos et al, 2013 ).…”
Section: Reduced α 5 Nicotinic Acetylcholine Receptor Expression Is a Risk Factor For Cocaine And Alcohol Usementioning
confidence: 99%